2020
DOI: 10.18632/aging.202184
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic acid protects oocytes against in vitro aging-induced deterioration and improves subsequent embryonic development in pigs

Abstract: As a pentacyclic triterpene in Centella asiatica , asiatic acid (AA) is a powerful antioxidant with many bioactivities. In the present research, we investigated whether AA has the potential to rescue the decrease in porcine oocyte quality that occurs during in vitro aging (IVA). Mature porcine oocytes were collected and then continuously cultured for an additional 24 h or 48 h with or without AA in maturation medium as an IVA model. The results revealed that AA sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In addition to heart, kidney and liver are negatively affected following DOX administration due to an increase in oxidative stress and inflammation [92,93]. Asiatic acid (AA) is another phytochemical that has been under attention due to its efficacy in preventing ageing, improving wound healing and exerting anti-tumor activity [94][95][96][97]. Recently, it has been shown that AA possesses high antioxidant potential that is of importance in reducing toxic effects of DOX against major organs of body.…”
Section: Natural Compounds In Ameliorating Doxorubicin-mediated Toxicitymentioning
confidence: 99%
“…In addition to heart, kidney and liver are negatively affected following DOX administration due to an increase in oxidative stress and inflammation [92,93]. Asiatic acid (AA) is another phytochemical that has been under attention due to its efficacy in preventing ageing, improving wound healing and exerting anti-tumor activity [94][95][96][97]. Recently, it has been shown that AA possesses high antioxidant potential that is of importance in reducing toxic effects of DOX against major organs of body.…”
Section: Natural Compounds In Ameliorating Doxorubicin-mediated Toxicitymentioning
confidence: 99%
“…Our results showed that FA alleviated the decrease in MMP and partially restored mitochondrial function in aged oocytes. These results provide evidence that exogenous antioxidant supplementation can improve mitochondrial function in aged oocytes and thus promote oocyte developmental potential [ 42 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 92%
“…Mitochondria are a site of energy metabolism and are involved in cell apoptosis and death. Several studies have shown that mitochondrial function influences oocyte developmental potential and is associated with subsequent embryonic development, such as that of PA, IVF, and SCNT embryos (Liang et al, 2018;An et al, 2019;Hu et al, 2020;Nie et al, 2020). Recent research has suggested that ferroptosis can lead to mitochondrial dysfunction, including loss of the MitoMP, enhanced mitochondrial fragmentation, and reduced mitochondrial respiration, in neuronal HT22 cells and mouse embryonic fibroblasts (Jelinek et al, 2018).…”
Section: Discussionmentioning
confidence: 99%